Exploring paediatric rheumatology care: a ten-year retrospective analysis of the patient population in Ghana - Dey, D.; Katso, B.; Baah, A.; Isaaka, S.; Amoako, E. (Pediatric Rheumatology, 2024)
Background Rheumatic diseases can seriously impact children’s general health, development, and growth. However, due to a lack of resources, paediatric rheumatology is a largely underdeveloped speciality in many African nations. Children with rheumatic disorders face obstacles in accessing specialized medical care, including lack of specialists, care centres, medication access, and limited research and education to increase understanding of paediatric rheumatic disease among healthcare practitioners. This study described the disease characteristics, prevalence, and challenges faced by paediatric rheumatic disease patients receiving care at a teaching hospital in Accra, Ghana. Methods A retrospective record-based study was conducted among all paediatric cases presenting to the rheumatology clinic of the Korle Bu Teaching Hospital (KBTH) from January 2011 to December 2021. Data collected include clinical features, laboratory findings at disease presentation, andtherapeutic regimens prescribed per standard guidelines and experiences. Results A total of 121 cases were identified as of 2021, indicating a point prevalence of 0.0011%. The majority (73%) were females with a mean age of 13.4 ± 3.2 years. The mean duration of symptoms in months experienced by patients before being successfully referred to a rheumatologist was 18 months. There were significant differences between referred and confirmed diagnoses, especially in cases involving mixed connective tissue diseases (MCTD), systemic lupus erythematosus (SLE), and juvenile dermatomyositis (JDM), suggesting that these conditions may be underrecognised. Arthralgia and arthritis were the most common presenting symptoms. More than three-quarters (86.8%) of the cases studied were treated with steroids (oral or intravenous). In cases requiring immunosuppressive therapy, methotrexate was the most commonly prescribed in 33.9% of instances. Mortality was recorded at 8.3%, with the majority involving SLE cases. Most (95.7%) of the primary caregivers expressed positive experiences regarding care received at the adult rheumatology clinic. Conclusion There were significant delays in diagnosis and diagnostic accuracy for patients with paediatric rheumatic disease (PRD). This highlights the pressing need for strengthening paediatric rheumatology services in Africa, including increasing awareness about these conditions among the public and healthcare providers to improve early diagnosis and quality of life for children with these conditions.
Research Article
Keywords: Paediatric rheumatic disease; Africa; Rheumatology; Disease characteristics; Teaching hospital